THE EFFECT OF GIVING BEETROOT PUDDING (BETA VULGARIS L) ON HEMOGLOBIN LEVELS IN ADOLESCENT GIRLS WITH ANEMIA AT THE PAOPALE DAYA POLINDES-MADURA - Tety Ripursari; Nita Dwi Astikasari; Rike (Universitas STRADA Indonesia, 2025)
Anemia is a condition where the number of red blood cells in the body is insufficient. Usually due to malnutrition (iron). Adolescent girls have a higher risk of experiencing anemia compared to adolescent boys because adolescent girls menstruate every month which puts them at risk of losing iron. Beetroot made into pudding can be a non pharmacological alternative in treating anemia. The purpose of this study was determine the effect of giving beetroot pudding on increasing hemoglobin levels in adolescent girls with anemia at the Paopale Daya-Madura health clinic. This tipe of research is quantitative, using a Quasi Experimental method with a one group pre test post test. The sampling technique in this study was Purposive sampling and obtained 30 respondents with anemia. The sample was obtained according to the inclusion by interview.